6th annual Southbank Arts Trail - Panayides, Angelos (My University, 2026)
Participation with a mediascape and a contribution to the live brief given by Pervasive Media Studios in collaboration and the module Developing Practice of my MA studies. A weekend of arts and performance in homes, churches, community centres and pubs around Southville, Bedminster and Ashton. An interactive environment made up of video, audio, images, and text based on my narrative. Participants used PDA to move around, the device sensed their position and activated the appropriate media files associating their positions from a GPS system.